In the World of Potentiality: Gombrowicz, Pinter, Beckett, and Różewicz - Krajewska, Anna (Przestrzenie Teorii, 2024)
This article attempts to analyze Witold Gombrowicz`s, Harold Pinter`s, Samuel Beckett`s, and Tadeusz Różewicz’s works by using methods that are associated with performative literary studies. The author refers to concepts of quantum physics and introduces a new aesthetic category, “entangled arts”. Among these arts are, for example, drama and theater, which are seen from an anti-binary perspective. This approach eliminates the traditional division of arts into the art of literature and performing arts, thus leading us to look on literature as a performing art. Therefore, the idea of “entangled arts” is not about “the synthesis of arts”, but about their unresolvedness and an act of reading which requires one to simultaneously exist and be active in two (or more, potentiality) different realities, for example, in a digital and imagined world, or in film and on stage.